Delivery of microRNA-33 Antagomirs by Mesoporous Silica Nanoparticles to Ameliorate Lipid Metabolic Disorders - Tao, Yaoye; Xu, Shengjun; Wang, Jianguo; Xu, Li; Zhang, Chenzhi; Chen, Kangchen; Lian, Zhengxing; Zhou, Junbin; Xie, Haiyang; Zheng, Shusen; Xu, Xiao (Frontiers in Pharmacology, 2020)
Lipid metabolic disorders have become a major public-health concern across the world. Fatty liver and dyslipidemia are major manifestations of these disorders. Recently, MicroRNA-33 (miR-33), a post-transcriptional regulator of genes involved in cholesterol efflux and fatty acid oxidation, is being considered as a good therapeutic target for these disorders. However, the traditional methods of gene therapy impede their further clinical transformation into a mature treatment system. To counter this problem, in this study, we used mesoporous silica nanoparticles (MSNs) as a nanocarriers to deliver miR-33 antagomirs developing nanocomposites miR-MSNs. We observed that the hepatocellular uptake of miR-33 antagomirs increased by ~5 times when they were delivered using miR-MSNs. The regulation effects of miR-MSNs on miR-33 and several genes involved in lipid metabolism were confirmed in L02 cells. In high-fat diet fed mice, miR-33 intervention via miR-MSNs lowered the serum triglyceride levels remarkably by 18.9% and reduced hepatic steatosis. Thus, our results provide a proof-of-concept for a potential strategy to ameliorate lipid metabolic disorders.